2022
DOI: 10.3390/nu14112354
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Mortality in Older Hemodialysis Patients

Abstract: (1) Sarcopenia is a progressive loss of skeletal muscle mass and strength. The aim of this study was to determine the association of sarcopenia, defined according to the Working Group on Sarcopenia in Older People (EWGSOP2) diagnostic criteria, with mortality at 24 months in very elderly hemodialysis patients. (2) A prospective study was conducted in 60 patients on chronic hemodialysis who were older than 75 years. Sarcopenia was diagnosed according to EWGSOP2 criteria. Additionally, clinical, anthropometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
3
18
1
Order By: Relevance
“…In addition, mitochondrial dysfunction and hormonal changes caused by aging are also related to sarcopenia [5]. Our findings on the relationship between age and sarcopenia are consistent with previous studies [6,8,35]. However, there are some controversies, Wang et al [14] systematic review have shown the age of HD patients was no significant influence on sarcopenia prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, mitochondrial dysfunction and hormonal changes caused by aging are also related to sarcopenia [5]. Our findings on the relationship between age and sarcopenia are consistent with previous studies [6,8,35]. However, there are some controversies, Wang et al [14] systematic review have shown the age of HD patients was no significant influence on sarcopenia prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…Sarcopenia is characterized by a gradual decline in physical performance, strength, and skeletal muscle mass (1,2). It has a prevalence of between 28.5% and 40.3% in patients receiving hemodialysis (3)(4)(5)(6)(7) and results in poor clinical outcomes (7)(8)(9). The complex pathophysiology of sarcopenia may be exacerbated by metabolic acidosis, oxidative stress, accumulated uremic toxins, inflammation, insulin resistance, malnutrition, protein restriction, decreased appetite, myostatin overexpression, ubiquitination, and physical inactivity (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to age-related processes, sarcopenia in potential KT recipients is also worsened by various factors, including malnutrition, metabolic acidosis, accumulation of uremic toxins, and amino acid loss during dialysis, as well as typical low-threshold inflammation [34]. Malnutrition is very common in patients requiring dialysis and leads to sarcopenia in these patients by reducing muscle mass and strength as well as physical performance [35].…”
Section: Discussionmentioning
confidence: 99%